Analisis Pendekatan Teks dan Konteks dalam Penentuan Pembagian Waris Islam - Khaeron Sirin (Universitas Islam Negeri Jakarta, 2013)
Abstract: Analysis of a Text and Context Approach within the Formulation of Islamic Inheritance Distributions. For about fourteen centuries Islamic inheritance law has always been regarded as a qat‘î doctrine which covers for ijtihad and should be taken for granted. However, changes and developments over time, the existence of Islamic inheritance in the Quran have started to be claimed. To some liberalists and feminist activists, the law on Islamic inheritance is a product of salaf scholars to be regarded as rules that tend to be discriminative—just like the discrediting and prejudicing the rights of women—and not oriented towards human justice. Therefore, the provisions of Islamic inheritance need to be reviewed, even deconstructed by considering the social development of society.Keywords: Islamic law, justice, inheritance, tafsîrAbstraksi: Analisis Pendekatan Teks dan Konteks dalam Penentuan Pembagian Waris Islam. Selama lebih kurang empat belas abad hukum kewarisan Islam selalu dianggap sebagai doktrin yang bersifat qat‘î yang menutup rapat ruang ijtihad dan harus diterima secara taken for granted. Namun seiring perubahan dan perkembangan zaman, eksistensi hukum kewarisan Islam dalam Alquran mulai digugat. Oleh sebagian pemikir liberal dan aktivis feminisme, hukum kewarisan Islam produk ulama salaf dianggap sebagai aturan yang cenderung diskriminatif—semisal mendiskreditkan dan merugikan hak-hak perempuan—dan tidak berorientasi pada keadilan manusia. Karenanya, ketentuan hukum waris Islam tersebut harus ditafsir ulang, bahkan didekonstruksi dengan mempertimbangkan perkembangan sosial masyarakat.Kata Kunci: hukum Islam, keadilan, kewarisan, tafsirDOI: 10.15408/ajis.v13i2.941